Rupture Directivity of Moderate Earthquakes Along the Main Marmara Fault Suggests Larger Ground Motion Towards Istanbul - Xiang Chen; Patricia Martínez‐Garzón; Grzegorz Kwiatek; Yehuda Ben‐Zion; Marco Bohnhoff; Fabrice Cotton (Geophysical Research Letters)
Abstract Analysis of earthquake rupture directivity provides key information for seismic hazard and risk assessment, particularly for faults near urban areas. We analyze directivity patterns for 31 well‐constrained ML≥ 3.5 earthquakes along the Main Marmara Fault, in direct proximity to Istanbul. We calculate source mechanisms with a waveform modeling approach and analyze earthquake directivity from apparent source‐time functions using empirical Green's functions. Most of the strike‐slip earthquakes to the west of the Princes Islands segment display a predominantly asymmetric rupture toward the east with the median directivity trending 85°, consistent with the Main Marmara Fault strike. Consequently, earthquake ground shaking may be more pronounced toward Istanbul. This holds potentially for a large earthquake on the Main Marmara Fault which is late in its seismic cycle. Our results motivate the importance of evaluating the impact of eastward asymmetric ruptures on the probabilistic seismic hazard and risk assessment around Istanbul.